Students’ opinions on working in rural practice in Slovenia - Petrovcic, Rok (Family Medicine & Primary Care Review, 2016)
Background. All over the world, there is a lack of interest for specialty training in family medicine and for work in rural practice. Objectives . The objective of our study was to survey the opinion of medical students of the Maribor Medical Faculty, Slovenia, about rural medicine. Material and methods . This was a qualitative study. A semi-structured questionnaire with open-ended questions was used. In the period from December 2013 to February 2014, an electronic form was forwarded via e-mail to a stratified sample of 30 students of the Maribor Medical Faculty. Results. 21 students (70%) participated. Students stated several conditions that would make them work in rural practice. Their accounts were summarized as organizational (e.g. work hours, number of patients), infrastructural (e.g. equipment), local (e.g. cost of living) or personal (e.g. employment opportunities for their partner). Students associate rural practice with hard work, where physicians have to rely on their own abilities. Students see rural doctors as versatile personalities, knowledgeable, resourceful, optimistic, hard working and smart, but also as unambitious and elderly. Students connect rural practice with greater responsibility, diverse pathology, less availability of equipment and with less support for diagnostics. 15 (71%) of the surveyed students want more emphasis placed on rural medicine in the undergraduate curriculum and electives. The reasons for accepting a rural scholarship would generally depend on the location for which it was offered and if it was tendered for the desired specialist training. Conclusions . Students should be presented with opportunities for personal and professional development in rural areas during undergraduate programs. Rural scholarship programs need to be strengthened.